Pengembangan Kompetensi Nilai dan Sikap Kebersamaan dalam Pembelajaran PPKn Melalui Strategi Card Sort - Amharulloh, Zaqiyan; Muthali’in, Achmad (Sosial Horizon: Jurnal Pendidikan Sosial, 2024)
This research aims to describe the development of value competencies and attitudes of togetherness in Civics learning through the Card Sort strategy for XC class students at SMA Muhammadiyah Boarding School Zam-Zam Cilongok. This research uses descriptive research with a qualitative approach. This research design uses case studies of data collection techniques interviews with sources, observation of learning activities, and photo documentation of activities which are then carried out triangulation data validity. The results of the research obtained by the researcher that the teacher has applied the card sort strategy in Civics learning with material related to elements in the indicators of togetherness. So that by presenting the results of student answers in turn and providing mutual feedback, students can increase their self-confidence. The obstacles to the application of this strategy are the lack of time allocation, students do not understand the direction of the teacher, the lack of conducive learning space and there is still individualism, less efficient discussion time, lack of social attitudes in students so that they look indifferent. Solutions that can be done based on these obstacles are that the teacher ensures that the learning instructions reach the students by going around the group in turn, giving a warning to students who do not participate in the discussion, the teacher reminds the rules and attitudes of the correct discussion.